Decentralized Adaptive Event-Triggered Control for a Class of Uncertain Systems With Deception Attacks and Its Application to Electronic Circuits - Sun, Yiming; Yu, Jinyong; Yu, Xinghu; Gao, Huijun (IEEE transactions on circuits and systems. I, Regular papers, 2020)
The problem of decentralized event-triggered control for a class of network-based state-dependent uncertain systems subject to network transmission delay and deception attacks is considered in this article. To reduce network load, a novel decentralized adaptive event-triggered scheme (AETS) is developed to transmit necessary sampled signals. During network transmission, a more practical deception attack phenomenon is considered, where the attack behaviors in different channels are governed by independent Bernoulli processes. Moreover, a set of improved data buffers are applied in the controller side to organize the decentralized triggered data and alleviate the impact of network transmission delay, such that the transmitted data can be utilized timely. Then, an integrated closed-loop system with state-dependent uncertainties is constructed by taking the AETS, deception attacks and data buffers into account. Sufficient conditions that guarantee the mean-square exponential stability of the closed-loop system are presented by employing the Lyapunov functional method, and the design criterion of the controller gain is given by an exact expression. Finally, the proposed method is applied to the control of electronic circuits to verify its practicability and effectiveness.